Non-covalently functionalized graphene strengthened poly(vinyl alcohol). (5th February 2018) - Wang, Xiaodong; Liu, Xianhu; Yuan, Hongyue; Liu, Hu; Liu, Chuntai; Li, Tingxi; Yan, Chao; Yan, Xingru; Shen, Changyu; Guo, Zhanhu
Abstract: In this work, non-covalently functionalized reduced graphene oxide (rGO) reinforced poly(vinyl alcohol) (PVA) nanocomposites were prepared by solution mixing. The agglomeration of graphene sheets was prevented by using surface modifying agent poly(sodium 4-styrenesulfonate) (PSS). The improved mechanical properties, including the Young's modulus and tensile strength of the PVA/rGO nanocomposites compared to neat PVA were attributed to the strong interactions between PVA and rGO such as π–π, hydrogen bonding, and CH–π. A 55% maximum increase in the modulus was obtained by adding only 0.1 wt% rGO, and an increase of 48% in tensile strength was achieved by adding 0.3 wt% rGO. In addition, the thermal properties of the nanocomposites were also improved, which was attributed to the restriction of graphene oxide (GO)/rGO sheets on the chain mobility of polymers on the GO/rGO sheets surface. Graphical abstract: Highlights: Non-covalently functionalized rGO PVA nanocomposites were prepared by solution mixing. Uniform dispersion of rGO was achieved with the assistance of poly(sodium 4-styrenesulfonate). Strong rGO-PVA interactions and effective load transfer from rGO to PVA significantly improved the mechanical properties.